2000
DOI: 10.1007/s003920050005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and angiographic outcome of patients with acute inferior myocardial infarction

Abstract: Primary PTCA is an appropriate reperfusion strategy in patients with RVI. Further comparative studies are required to compare the effectiveness of primary PTCA with early thrombolytic therapy in this high risk setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Atherosclerotic calcification is the most common form of calcific vasculopathy, and occurs as early as the second decade of life just after fatty streak formation (Stary et al, 1995). Small aggregates of crystalline calcium can be detected in developing lesions, and in adults past the fourth decade of life, greater lesion areas may be calcified (Stary, 2000). The degree of calcification correlates with the extent of atherosclerosis, with age, and hypertension as dominant risk factors for systemic calcified atherosclerosis (Allison et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerotic calcification is the most common form of calcific vasculopathy, and occurs as early as the second decade of life just after fatty streak formation (Stary et al, 1995). Small aggregates of crystalline calcium can be detected in developing lesions, and in adults past the fourth decade of life, greater lesion areas may be calcified (Stary, 2000). The degree of calcification correlates with the extent of atherosclerosis, with age, and hypertension as dominant risk factors for systemic calcified atherosclerosis (Allison et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some authors believe that the right ventricle damage is a powerful predictor of major cardiovascular episodes during follow-up, even after the infarction size has been normalized in the left ventricle---which can have a significantly greater mortality 46,47 ; others have not shown any short-term prognostic relations in the infarction of the right ventricle. 48,49 In sum right ventricle AMI can be reliably detected through CMR yet the prognostic meaning of late enhancement in the right ventricle remains unclear.…”
Section: Right Ventricle Infarctionmentioning
confidence: 99%
“…22 However, although the number of patients with RV infarction is small, these patients seem to have a higher risk of in-hospital mortality in the mechanical reperfusion era than during the fibrinolytic era. Figure 2 shows the changes in the in-hospital mortality rate and relative risk of RV infarction for in-hospital mortality between the fibrinolytic and mechanical reperfusion era; 8,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] An increase in the relative risk of RV infarction from 2.29 (95% CI 1.67-3.14) to 2.98 (95% CI 1.41-6.31) also occurred during this period. The precise explanation for the paradox remains unknown.…”
Section: Short-term Prognosismentioning
confidence: 99%
“…These data were derived from previously published meta-analyses, 21 which included many prospective or retrospective studies, assessing the impact of RV infarction in patients with acute MI up to June 2007, 8,[23][24][25][26][27][28][29][30][33][34][35][36] and two additional observational studies that met the same inclusion criteria up to June 2012. 31,32 of concomitant LV involvement, this study indicated that the mean optimal PWP, which corresponded to the maximum LV stroke work index in each patient, was 16 mmHg.…”
Section: Volume Replacementmentioning
confidence: 99%
See 1 more Smart Citation